Learning Modules with ARCS Keller Approach to Increase Children's Learning Interest and Motivation - Wicaksono, Phandhu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The 2023 Education Statistics data shows that 5.14% of elementary school students/equivalent had to repeat their education, one of the reasons being the inability to complete the lessons. The ARCS Keller learning method which provides a systematic and comprehensive approach can be an initiative step in stimulating interest and motivation in learning. This research is a case study conducted on 3 fifth-grade students at SDN Kotalama 5 who met the inclusion criteria with the aim of determining the description of students' interest and motivation in learning before and after learning using the learning module with the ARCS Keller approach. The instruments used were the Course Interest Survey (CIS) to determine the level of student interest in learning and the Teaching Materials Motivation Survey (IMMS) to determine the extent of student motivation in learning as well as observation sheets and interviews to obtain supporting data. All data were analyzed using quantitative descriptive methods. The results showed an increase in the average value of learning interest by 12.45% and learning motivation by 11.34%, followed by positive changes in attitudes in participating in learning. The use of learning modules with the ARCS Keller approach can increase students' interest and motivation in learning by helping students concentrate better, understand the material well, think critically, have self-confidence and achieve satisfaction in learning.